CINEMA IN JAMAICA – THE LEGACY OF THE HARDER THEY COME (Revue D’études Interculturelles De L’image, 2018)
Mainstream cinema representing Jamaica and Jamaicans has always made use of clichés and stereotypes. The emergence of a local Jamaican cinema—beginning in 1972 with Perry Henzell’s movie—immediately started to give a new image of the country and its inhabitants. From The Harder They Come up to most recent movies, Jamaican cinema has used consistent style, techniques, and themes to give a new vision of the country. Jamaican movies may have low production value, but they provide a more authentic representation of Jamaica’s culture. Viewing Jamaican movies gives the audience a sense of a small but growing cinematic tradition.